2007
DOI: 10.1093/icc/dtm020
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the propensity of academics to engage in informal university technology transfer

Abstract: Formal university technology transfer mechanisms, through licensing agreements, research joint ventures, and university-based startups, have attracted considerable attention in the academic literature. Surprisingly, there has been little systematic empirical analysis of the propensity of academics to engage in informal technology transfer. This paper presents empirical evidence on the determinants of three types of informal technology transfer by faculty members: transfer of commercial technology, joint public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
289
1
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(319 citation statements)
references
References 31 publications
(24 reference statements)
14
289
1
15
Order By: Relevance
“…As motivações secundárias dos pesquisadores estiveram ligadas à obtenção de fundos de pesquisa adicionais para manter estudantes e equipamentos dos seus laboratórios, bem como a ganhos financeiros (Link, Siegel, & Bozeman, 2007;Siegel et al, 2004). Um percentual de royalties maior para acadêmicos envolvidos em TTUE tende a estimulá-los; recompensas inadequadas são, por outro lado, uma barreira à eficácia deste processo (Baldini, 2010;Caldera & Debande, 2010).…”
Section: Intervenientes No Processo De Ttueunclassified
See 1 more Smart Citation
“…As motivações secundárias dos pesquisadores estiveram ligadas à obtenção de fundos de pesquisa adicionais para manter estudantes e equipamentos dos seus laboratórios, bem como a ganhos financeiros (Link, Siegel, & Bozeman, 2007;Siegel et al, 2004). Um percentual de royalties maior para acadêmicos envolvidos em TTUE tende a estimulá-los; recompensas inadequadas são, por outro lado, uma barreira à eficácia deste processo (Baldini, 2010;Caldera & Debande, 2010).…”
Section: Intervenientes No Processo De Ttueunclassified
“…A possibilidade de obter verbas adicionais para equipamentos, reagentes e alunos, entre outros recursos para realizar pesquisas de laboratório, foi muito valorizada pelos pesquisadores da PUCRS, tal como em outros casos investigados (Link et al, 2007;Santana & Porto, 2009;Segatto-Mendes & Mendes, 2006;Siegel et al, 2004 O patenteamento de resultados de pesquisa e a visão das possibilidades de ganhos incentivaram também certa competição entre os pesquisadores, gerando novas tentativas de patenteamento. A motivação para realizar pesquisas que resultaram em patentes foi ainda fruto da necessidade de produzir artigos científicos, um dos principais quesitos avaliados por órgãos de fomento à pesquisa do governo para aprovação de verbas com este fim.…”
Section: Principais Intervenientes No Processo De Ttue No Caso Pucrsunclassified
“…The TTO at a typical university serves as the broker between technology resulting from university research and its commercialisation through private interests. The main instruments for technology transfer have been patented inventions, licensed technologies and new ventures (Link and Siegel, 2005;Link et al, 2007). Identification and measurement of university technology transfer has been facilitated by the Association of University Technology Managers (AUTM) in the USA, which provides systematic and comprehensive measurement of the activities of each university's TTO (Association of University Technology Managers, 2004).…”
Section: Technology Transfermentioning
confidence: 99%
“…Several studies (Markmann et al, 2005;Phan & Siegel, 2006;Link et al, 2007;Geuna & Muscio, 2009;Mowery & Ziedonis, 2014;Anatan, 2015;Gervais et al, 2016) consider the technology transfer with a many-sided nature. According to Gilsing et al (2011), it has been demonstrated how a wide range of factors affects the transfer of technological knowledge from universities to industry.…”
Section: Technology Transfermentioning
confidence: 99%
“…There are a several formal technology transfer mechanisms, which include, but it is not limited to: collaborative research, research joint ventures, technology consulting, strategic alliances, licensing and acquisition, spin-off companies and incubators (Link et al, 2007, Markmann et al, 2005Muscio et al, 2014;Ranga et al, 2016). Geuna and Muscio (2009) point that universities are trying to promote the technology transfer with new mechanisms with the purpose of being succeeful in the third mission activities, related to new ventures or income from entrepreneurial activities such as the incubation of new ventures driven to society.…”
Section: Technology Transfermentioning
confidence: 99%